Towards AI-Integrated English Learning Activities: A TAM Analysis of Vocational Students' Behavioral Intention - Ansas, Velayeti Nurfitriana; Pradana, Handi; Fazhar Restu Fauzi; Betuah Anugerah; Wakhid Herri Nurcahyo; Muchdirin; Roro Ayu Fasha Dewatri (Southeast Asian Journal on Open and Distance Learning, 2024)
This research examines the influence of students' experiences using the artificial intelligence-based application Talk to GPT in learning to speak English and their motivation to use this technology. A total of 28 vocational school students participated in the study, utilizing questionnaires to measure their perceptions of the application's benefits, ease of use, and its impact on their motivation. The findings reveal that students experienced more efficient and engaging learning activities, supported by Talk to GPT's interactive features that provided personalized responses and immediate feedback, enhancing their fluency, vocabulary, pronunciation, and confidence in speaking English. The application's intuitive interface and ease of adaptability further facilitated a seamless learning experience, reducing technological barriers and increasing students' productivity. Moreover, the study demonstrated that students had a strong Behavioral Intention (BI) to continue using Talk to GPT and other AI-based tools for various educational purposes, signifying a positive shift in their acceptance and enthusiasm for integrating AI technologies into learning. These findings highlight the transformative potential of AI-powered applications in creating engaging, student-centered learning environments, fostering motivation, and encouraging the exploration of innovative educational tools, ultimately contributing to developing a more technologically integrated and dynamic curriculum.